Ecological network analysis metrics: The need for an entire ecosystem approach in management and policy. (15th May 2019) - Fath, Brian D.; Asmus, Harald; Asmus, Ragnhild; Baird, Dan; Borrett, Stuart R.; de Jonge, Victor N.; Ludovisi, Alessandro; Niquil, Nathalie; Scharler, Ursula M.; Schückel, Ulrike; Wolff, Matthias
Abstract: In this paper, we identified seven ecological network analysis (ENA) metrics that, in our opinion, have high potential to provide useful and practical information for environmental decision-makers and stakeholders. Measurement and quantification of the network indicators requires that an ecosystem level assessment is implemented. The ENA metrics convey the status of the ecological system state variables, and mostly, the flows and relations between the various nodes of the network. The seven metrics are: 1) Average Path Length (APL), 2) Finn Cycling Index (FCI), 3) Mean Trophic level (MTL), 4) Detritivory to Herbivory ratio (D:H), 5) Keystoneness, 6) Structural Information (SI), and 7) Flow-based Information indices. The procedure for calculating each metric is detailed along with a short evaluation of their potential assessment of environmental status.